A new mosasaurine specimen (Squamata, Mosasauridae) from the Upper Cretaceous of Antarctica with comments on the Weddellian diversity of Mosasaurinae - O'gorman, Jose Patricio; Bona, Paula; Canale, Juan Ignacio; Tineo, David; Fernández, Marta Susana; Cardenas, Magali; Reguero, Marcelo Alfredo (Alcheringa: An Australasian Journal of Palaeontology)
Mosasaurs were globally distributed throughout the Cretaceous oceans, including those surrounding Antarctica. A mosasaur humerus (IAA-Pv 819) from upper Maastrichtian beds of the López de Bertodano Formation of Antarctica is phylogenetically recovered in a mosasaurine polytomy as a close relative of Plotosaurus beninsoni and Mosasaurus spp. Comparisons between IAA-Pv 819 and other Weddellian mosasaurs reveal differences indicating that morphological disparity and taxonomic diversity of Antarctic mosasaurines may be higher than previously recognized. José Patricio O'Gorman [joseogorman@fcnym.unlp.edu.ar], Bona Paula [paulabona26@gmail.com], División Paleontología Vertebrados, Museo de La Plata, Universidad Nacional de La Plata, Paseo del Bosque s/n., B1900FWA, La Plata, Buenos Aires, Argentina; CONICET: Consejo Nacional de Investigaciones Científicas y Técnicas, Godoy Cruz 2290, C1425FQB, Ciudad Autónoma de Buenos Aires, Argentina. Juan Ignacio Canale [jicanale@unrn.edu.ar], Área Laboratorio e Investigación, Museo Municipal “Ernesto Bachmann”, Dr. Natali s/n, Q8311AZA Villa El Chocón, Neuquén, Argentina; CONICET: Consejo Nacional de Investigaciones Científicas y Técnicas, Godoy Cruz 2290, C1425FQB, Ciudad Autónoma de Buenos Aires, Argentina; Universidad Nacional de Río Negro (UNRN), Isidro Lobo 516, General Roca (8332), Río Negro, Argentina. David E. Tineo [tineo.d.e@gmail.com], Facultad de Ciencias Naturales y Museo, Universidad Nacional de La Plata, Calles 60 y 122 s/n, B1900FWA, La Plata, Buenos Aires, Argentina; CONICET: Consejo Nacional de Investigaciones Científicas y Técnicas, Godoy Cruz 2290, C1425FQB, Ciudad Autónoma de Buenos Aires, Argentina. Marta Susana Fernández [martafer@fcnym.unlp.edu.ar], División Paleontología Vertebrados, Museo de La Plata, Universidad Nacional de La Plata, Paseo del Bosque s/n., B1900FWA, La Plata, Buenos Aires, Argentina; CONICET: Consejo Nacional de Investigaciones Científicas y Técnicas, Godoy Cruz 2290, C1425FQB, Ciudad Autónoma de Buenos Aires, Argentina. Magali Cárdenas ...